Cloning of the gene for phosphoribulokinase activity from Rhodobacter sphaeroides and its expression in Escherichia coli. - Hallenbeck, P L (1987)
A 3.4-kilobase EcoRI restriction endonuclease fragment has been cloned from the facultatively photoheterotrophic bacterium Rhodobacter sphaeroides and shown to contain the structural gene (prkA) for phosphoribulokinase (PRK) activity. The PRK activity was characterized in Escherichia coli, and the product of the reaction was identified. The prkA gene was localized to a 1,565-base-pair EcoRI-PstI restriction endonuclease fragment and gave rise to a 33-kilodalton polypeptide both in vivo and in vitro. The gene product produced in E. coli was shown to be identical to the gene product produced in R. sphaeroides. The amino acid sequence for the amino-terminal region deduced from the DNA sequence confirmed that derived for partially purified PRK derived from both E. coli and R. sphaeroides. In addition, the 3.4-kilobase EcoRI restriction endonuclease fragment coded for a 37-kilodalton polypeptide of unknown function, and preliminary evidence indicates that this DNA fragment is linked to genes coding for other activities significant in photosynthetic carbon assimilation. The genetic organization and proposed operon structure of this DNA fragment are discussed.